Rehabilitation Nursing for heart transplant (rn4htx) - intervention project presentation - Maria Loureiro; Marta Costa; Emília Sola; Gonçalo Coutinho; Maria Manuela Martins; André Novo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Cardiac Rehabilitation (CR) is a multifactorial intervention, usually composed of structured physical exercise, psychological support and health education. The structuring in the different phases of CR for this specific population has not been deeply studied, with gaps in the scientific evidence regarding health gains resulting from CR programs. The caregiver / family literature is also scarce. The aim of this study is to identify in which domains rehabilitation nurses can intervene in order to develop health gains in heart transplant recipients and their caregivers/family. Method: To make this intervention operational, Doran's The Quality Health Outcomes Model will be used, in the component of results sensitive to nursing care. Two studies will be carried out concurrently, one aimed at the cardiac rehabilitation of the transplanted person (phases 1, 2 and 3) and the other focusing on the cardiac rehabilitation of the caregiver / family. The methodologies used will be the scoping review, the case report, the exploratory study and the randomized clinical study (with intervention group and control group). Discussion/Expected Results: The Rehabilitation Nursing in Cardiac Transplant Program (ERtxC) will be built and implemented, in its different phases, during the years 2021 and 2022. It is estimated that the program can be accessed by 150 heart transplant patients and their respective families / caregiver. Conclusion: At the end of the year 2022, it is estimated to have reached the end of this program, with the respective assessment of health gains. After validation of this program, an attempt will be made to permanently create this offer in a systematic way for all people undergoing heart transplantation in Portugal.